Administration of Intra-Coronary Adenosine before Stenting for Prevention of No Reflow/Slow Flow in Patients with Acute ST Elevation MI - Ayu, Muhammad Ejaz; Khan, Kashif; Abbasi, Waleed Ahmed; Salam Azad, Muhammad Abdus; Shabbir, Asma; Khan Niazi, Gul Zaman (Indus Journal of Bioscience Research, 2025)
Background and Aim: The phenomenon of no-reflow/slow-flow during primary percutaneous coronary intervention (PCI) in acute ST-elevation myocardial infarction (STEMI) patients remain a challenging complication causing adverse myocardial perfusion and outcomes. The administration of intra-coronary adenosine, anti- platelet and anti-inflammatory vasodilator has been recommended as latent strategy to prevent and mitigate this complication. The aim of the present study was to assess the efficacy of intra-coronary adenosine administration before stenting in preventing no-reflow/slow-flow in patients presenting with acute STEMI undergoing primary PCI. Patients and Methods: A questionnaire-based case-control study investigated 100 patients (50 in the adenosine group and 50 in the control group) at Rawalpindi Institute of Cardiology, Rawalpindi for the duration of three months, from December 21, 2024 to March 20, 2025. STEMI patients with chest pain duration <12 hours and requiring stenting enrolled. Demographic details, comorbidities such as DM, HTN, dyslipidemia, stroke, and obesity, medication use, tobacco usage, medical/surgical/family history, socioeconomic factors, and procedure-related variables including occlusion level, thrombus burden, use of thrombus aspiration, distal drug delivery, TIMI flow grade, and adenosine dose recorded. SPSS v23 used for data analysis. Results: 100 patients were randomly assigned to two groups; Group-A (N=50) administrated with adenosine and Group-B (N=50) administrated with standard treatment or control group. Both groups had comparable results in baseline and clinical characteristics with no significant differences (p > 0.05). Renal function parameters such as serum creatinine (89.2 ± 18.5 vs. 91.4 ± 20.1 mmol/L) and glomerular filtration rate (76.3 ± 15.2 vs. 73.1 ± 16.8 ml/min/1.73m²), showed no significant difference between the adenosine and control groups, respectively (p > 0.05). Adenosine group had significantly frequent cases (90%) of final TIMI flow grade III compared to control group (70%) (p=0.01). However, no significance difference observed in angiographic findings (culprit vessels and thrombus burden). The prevalence of no-reflow phenomenon was 6% in adenosine group compared to control group (24%) (p=0.02). Distal drug administration via micro catheter was significantly higher (92%) in adenosine group compared to control group (10%), (p<0.001). Stent size, thrombus aspiration, lesion characteristics, and pre- and post-dilation had no significant differences in both groups. Conclusion: The pre-stenting administration of intra-coronary adenosine improved the procedural outcomes in acute STEMI patients underwent PCI significantly reduces the prevalence of no-reflow/slow-flow. These observations support the evidence of adenosine clinical utility as a preventive strategy for high-risk STEMI intervention.